2017
DOI: 10.24190/issn2564-615x/2017/03.09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of drought responses in Phaseolus vulgaris (common bean) and P. coccineus (runner bean) cultivars

Abstract: Genetic improvement of crop drought tolerance has become an urgent need for increasing agricultural yields and food production, to feed a growing human population in the context of global climate change. To get insights into the most relevant mechanisms underlying drought resistance in beans, we have analysed the responses to water deficit of three Phaseolus vulgaris (common bean) and one P. coccineus (runner bean) cultivars, focusing on the accumulation of specific osmolytes, a conserved response to abiotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…In the Sedum taxa studied in the present work, however, the relative stress-induced increase in Pro contents was negatively correlated to the relative degree of tolerance: it was the largest in the most sensitive species, S. album, followed by S. sediforme, whereas no significant change was observed for the most tolerant S. spurium. Negative correlations between Pro accumulation and the relative degree of tolerance have been reported for other taxa, for example for different bean cultivars (Morosan et al 2017). In any case, Pro concentrations measured in all four Sedum species were too low, both in the controls and the stressed plants, to have any relevant osmotic effect.…”
Section: Discussionmentioning
confidence: 57%
“…In the Sedum taxa studied in the present work, however, the relative stress-induced increase in Pro contents was negatively correlated to the relative degree of tolerance: it was the largest in the most sensitive species, S. album, followed by S. sediforme, whereas no significant change was observed for the most tolerant S. spurium. Negative correlations between Pro accumulation and the relative degree of tolerance have been reported for other taxa, for example for different bean cultivars (Morosan et al 2017). In any case, Pro concentrations measured in all four Sedum species were too low, both in the controls and the stressed plants, to have any relevant osmotic effect.…”
Section: Discussionmentioning
confidence: 57%
“…Agriculture 2019, 9, x FOR PEER REVIEW 3 of 18 [19][20][21], among many others. Similar comparative studies were performed by our group on different species of Phaseolus [22][23][24]. In this work, we present an exhaustive morphological characterization of 24 accessions of common bean local landraces stored at the seed bank of COMAV; they were chosen, maximizing their geographical origin and their morphological diversity, for studying their adaptation to drought and salinity (manuscript in preparation).…”
Section: Seed Materialsmentioning
confidence: 84%
“…The result for determination of stress signature under all of the nutrient limitations by the random forest decision tree model indicates a prominent role of proline. Proline has been referred to as a stress signal in numerous studies with plants (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized from studies that proline affects signaling pathways through the mechanism of increased production of reactive oxygen species (ROS) in mitochondria (22). Besides plants (23,24), the same biological function has been observed in worms, apoptosis, tumor suppression, and cell survival in animals. In human tumorogenesis and tumor development it has been found that proline degradative pathway, plays a special role in (25).…”
Section: Discussionmentioning
confidence: 99%